The Exclusion of Minority Languages in Communicating COVID-19 Information in a Multilingual Context: A Case Study of Five Towns in the Far North and Adamawa Regions in Cameroon - Tasah, James N. (European Scientific Journal, ESJ, 2026)
Although Cameroon is a multilingual nation, the majority of its citizens were sensitized exclusively in official languages when the COVID-19 crisis broke out in the country in March 2020. The advent of COVID-19 clearly confirmed the government’s inability to provide information to all citizens in their respective minority languages. This study seeks to find out if the use of official languages was effective in the sensitization of the population of Mokolo, Maroua, Meiganga, Ngaoundere and Yagoua, both in the Far North and Adamawa regions, against the pandemic. The study uses Chumbow’s (2012) Social Engineering theory. Data were obtained from participant observation, focus group discussions, and questionnaire administration to 250 respondents. The findings revealed that the majority, 123(49.2%), of the respondents preferred information on COVID-19 in Fulfulde and 99(39.6%) in their respective minority languages, while only a minority, 25(10%), were comfortable with the information in French and 3 (1.2%) in English.